Optical laminate, and polarizing plate, display panel, and image display device using the same

JP7641710B2Active Publication Date: 2025-03-07DAI NIPPON PRINTING CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020091548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-26
Publication Date
2025-03-07
Estimated Expiration
2040-05-26

AI Technical Summary

Benefits of technology

【0009】 本発明の光学積層体、並びに、これを用いた表示パネル及び画像表示装置によれば、ポジティブA層の位相差が経時的に変化することを抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641710000008
    Figure 0007641710000008
  • Figure 0007641710000009
    Figure 0007641710000009
  • Figure 0007641710000010
    Figure 0007641710000010
Patent Text Reader

Abstract

To provide an optical laminate that can prevent the phase difference of a positive A layer from changing over time.SOLUTION: An optical laminate has a positive A layer and an ultraviolet absorption layer adjacent to the positive A layer. The ultraviolet absorption layer is preferably an alignment layer for the positive A layer. The optical laminate preferably has a positive C layer on the opposite side of the ultraviolet absorption layer based on the positive A layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical laminate, and a polarizing plate, a display panel, and an image display device using the same. [Background technology]

[0002] Electroluminescent display elements (hereinafter sometimes abbreviated as EL elements) have a wide viewing zone due to their self-luminous nature and consume less power than plasma light-emitting elements, and therefore have been put to practical use in image display devices in recent years. In particular, organic EL elements, which use organic compounds as light-emitting materials, can reduce the applied voltage significantly compared to inorganic EL elements, which use inorganic compounds, and therefore various studies are being conducted on their use as display devices.

[0003] Organic EL elements are generally known to have a structure in which a first electrode, a light-emitting layer, and a second electrode are sequentially laminated on a transparent substrate. There are bottom-emission types in which a transparent electrode is used as the first electrode and a metal electrode is used as the second electrode, and light emitted from the light-emitting layer is extracted from the transparent substrate side, and top-emission types in which a metal electrode is used as the first electrode, a transparent electrode is used as the second electrode, and light emitted from the light-emitting layer is extracted from the second electrode side (e.g., Patent Documents 1 and 2, etc.). In organic EL elements, regardless of the type, metal electrodes with excellent reflectivity are often used to efficiently utilize the light from the light-emitting layer. However, organic EL elements using such metal electrodes may have a high degree of external light reflection, resulting in reduced contrast. In addition, the reduction in contrast due to external light reflection is also a problem in display devices other than those including organic EL elements (for example, display devices in which a resistive touch panel with many air interfaces is arranged on a display element).

[0004] Various methods for suppressing external light reflection in display devices have been investigated. One such method is known to use a so-called circular polarizing plate formed by laminating a retardation plate and a polarizing plate (for example, Patent Documents 3 and 4, etc.). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-294421 A [Patent Document 2] JP 2007-80604 A [Patent Document 3] JP 2014-206684 A [Patent Document 4] JP 2015-57666 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, image display devices have been required to have higher quality and durability. However, in recent years, it has been found that the quality of the retardation layer (anti-reflection performance in the case of circular polarizers such as those in Patent Documents 3 and 4) deteriorates over time. [Means for solving the problem]

[0007] As a result of intensive research, the inventors have found that the quality (e.g., anti-reflection performance) of the retardation layer is likely to deteriorate when exposed to a high-temperature environment or an environment exposed to sunlight for a long period of time, and further found that the cause of this is a change in the retardation of the retardation layer. As a result of further intensive research, the inventors have found that by disposing an ultraviolet absorbing layer in contact with the positive A layer, it is possible to suppress the change in retardation of the positive A layer over time, thereby completing the present invention.

[0008] The present invention provides the following [1] to

[14] . [1] An optical laminate comprising a positive A layer and an ultraviolet absorbing layer in contact with the positive A layer. [2] The optical laminate according to [1], wherein the ultraviolet absorbing layer is an alignment layer for the positive A layer. [3] The optical laminate according to [2], wherein the thickness of the ultraviolet absorbing layer is 0.2 μm or more and 2.0 μm or less. [4] The optical laminate according to [2] or [3], which has a positive C layer on the opposite side of the positive A layer from the ultraviolet absorbing layer. [5] The optical laminate according to [1], further comprising a positive C layer on the opposite side of the ultraviolet absorbing layer to the positive A layer. [6] The optical laminate according to [5], wherein the positive C layer is in contact with the ultraviolet absorbing layer. [7] The optical laminate according to [6], wherein the ultraviolet absorbing layer is an alignment layer for the positive C layer. [8] The optical laminate according to any one of [5] to [7], wherein the ultraviolet absorbing layer has a thickness of 2.0 μm or more and 5.0 μm or less. [9] The optical laminate according to any one of [1] to [8], having a transmittance at a wavelength of 405 nm of 2.0% or more and 80.0% or less.

[10] The optical laminate according to any one of [1] to [9], wherein when the in-plane retardation of the positive A layer at a wavelength of 550 nm is defined as Re(550), Re(550) is 135 nm or more and 150 nm or less.

[11] The optical laminate according to any one of [1] to

[10] , wherein the in-plane retardation of the positive A layer at a wavelength of 450 nm is defined as Re(450), the in-plane retardation of the positive A layer at a wavelength of 550 nm is defined as Re(550), and the in-plane retardation of the positive A layer at a wavelength of 650 nm is defined as Re(650), and the relationship of the following formula (A) is satisfied. Re(450) <Re(550)<Re(650) (A)

[12] A polarizing plate having a polarizer, a transparent protective plate A arranged on one side of the polarizer, and a transparent protective plate B arranged on the other side of the polarizer, wherein either the transparent protective plate A or the transparent protective plate B is an optical laminate described in any one of [1] to

[11] .

[13] A display panel comprising the optical laminate according to any one of [1] to

[11] disposed on a light exit surface of a display element.

[14] The display panel according to

[13] , wherein the ultraviolet absorbing layer is disposed farther from the display element than the positive A layer. An image display device comprising the display panel described in

[15] ,

[13] or

[14] .

Advantages of the Invention

[0009] According to the optical laminate of the present invention, and the display panel and the image display device using the same, it is possible to suppress the change with time of the retardation of the positive A layer.

Brief Description of the Drawings

[0010] [Figure 1] It is a cross-sectional view showing one embodiment of the optical laminate of the present invention. [Diagram 2] It is a cross-sectional view showing another embodiment of the optical laminate of the present invention. [Diagram 3] It is a cross-sectional view showing one embodiment of the polarizing plate of the present invention. [Figure 4] It is a cross-sectional view showing one embodiment of the display panel of the present invention.

Modes for Carrying Out the Invention

[0011] Hereinafter, embodiments of the present invention will be described. In this specification, the notation "AA to BB" means "AA or more and BB or less".

[0012] Also, in this specification, the positive A layer is a layer that satisfies the relationship Nx>Ny≒Nz when the refractive index in the X-axis direction, which is the axial direction with the highest refractive index along the in-plane of the layer, is Nx, the refractive index in the Y-axis direction perpendicular to the X-axis in the in-plane direction of the layer is Ny, and the refractive index in the thickness direction of the layer is Nz. Further, in this specification, the positive C layer is a layer that satisfies the relationship Nx≒Ny<Nz.

[0013] Also, in this specification, the "in-plane retardation at a wavelength of 450 nm" may be denoted as "Re(450)", the "in-plane retardation at a wavelength of 550 nm" as "Re(550)", the "in-plane retardation at a wavelength of 650 nm" as "Re(650)", and the "retardation in the thickness direction at a wavelength of 550 nm" as "Rth(550)". The in-plane retardation (Re) and the retardation in the thickness direction (Rth) can be calculated from Nx, Ny, Nz and the thickness d (nm) of the retardation layer by the following formula. In-plane phase difference (Re)=(Nx-Ny)×d Retardation in the thickness direction (Rth) = ((Nx + Ny) / 2-Nz) × d

[0014] In this specification, unless otherwise specified, the measurement of the in-plane retardation and other measurements and evaluations are performed in an atmosphere with a temperature of 23° C.±5° C. and a humidity of 40% to 65%. Furthermore, before the measurement and evaluation, the sample is exposed to the above atmosphere for 30 minutes or more.

[0015] [Optical laminate] The optical layered body of the present invention comprises a positive A layer and an ultraviolet absorbing layer in contact with the positive A layer.

[0016] 1 and 2 are cross-sectional views showing an embodiment of the optical laminate of the present invention. The optical laminate 100 in FIG. 1 and FIG. 2 has a positive A layer 10 and an ultraviolet absorbing layer 20 in contact with the positive A layer. 1 has a positive C layer 30 on the opposite side of the ultraviolet absorbing layer 20 with respect to the positive A layer 10. In FIG. 1, the positive A layer 10 and the positive C layer 30 are laminated via an adhesive layer 40. 2 has a positive C layer 30 on the opposite side of the positive A layer 10 with respect to the ultraviolet absorbing layer 20. In FIG. 2, the positive C layer 30 and the ultraviolet absorbing layer 10 are laminated in contact with each other.

[0017] The optical laminate of the present invention only needs to have a positive A layer and an ultraviolet absorbing layer in contact with the positive A layer, and is not limited to the laminate configuration of Figures 1 and 2. For example, the optical laminate of the present invention may not have a positive C layer, or may have a layer that is not included in the optical laminate of Figures 1 and 2.

[0018] <Positive A layer> The positive A layer is a layer that satisfies the relationship Nx>Ny≒Nz. The positive A layer preferably contains a constitutional unit derived from a liquid crystal compound as a main component, which means that the main component is 50% by mass or more of the total solid content of the positive A layer, preferably 70% by mass or more, and more preferably 90% by mass or more.

[0019] The liquid crystal compound forming the positive A layer and the positive C layer described later preferably contains a polymerizable liquid crystal compound having a polymerizable functional group in the molecule. By having a polymerizable functional group, it is possible to polymerize and fix the liquid crystal compound, so that the alignment stability is excellent and the retardation is less likely to change over time. In addition, it is more preferable that the polymerizable liquid crystal compound has two or more polymerizable functional groups in the molecule. By having two or more polymerizable functional groups, the three-dimensional alignment of the liquid crystal compound can be more stable, and the retardation is less likely to change over time. However, the suppression of the retardation change over time described above is insufficient when the ultraviolet absorbing layer is not in contact with the positive A layer. This point will be specifically explained in the embodiment of the ultraviolet absorbing layer.

[0020] Examples of the polymerizable functional group include those that polymerize by the action of ionizing radiation such as ultraviolet rays and electron beams, or heat. Examples of these polymerizable functional groups include radically polymerizable functional groups. Representative examples of radically polymerizable functional groups include functional groups having at least one addition-polymerizable ethylenically unsaturated double bond, and specific examples include vinyl groups with or without substituents, acrylate groups (a general term including acryloyl groups, methacryloyl groups, acryloyloxy groups, and methacryloyloxy groups), and the like. In addition, as the polymerizable functional group, a generally known cationic polymerizable functional group may be used, and specific examples thereof include an alicyclic ether group (epoxy group, oxetanyl group, etc.), a cyclic acetal group, a cyclic lactone group, a cyclic imino ether group, a cyclic thioether group, a spiro orthoester group, a vinyloxy group, etc. Among these, an alicyclic ether group and a vinyloxy group are preferred, and an epoxy group, an oxetanyl group, and a vinyloxy group are more preferred.

[0021] In addition, the liquid crystal compound is particularly preferably one having a polymerizable functional group at the end. By using such a liquid crystal compound, for example, the ends of the liquid crystal compound can be polymerized with each other to be three-dimensionally aligned, so that the positive A layer or the positive C layer can be made stable and excellent in expressing optical properties.

[0022] The liquid crystal compound can be used alone or in combination of two or more. When using one type alone, the liquid crystal compound is preferably a polymerizable liquid crystal compound. When using two or more types in combination, it is preferable that at least one of them is a polymerizable liquid crystal compound, and it is more preferable that all of them are polymerizable liquid crystal compounds.

[0023] The liquid crystal compound of the positive A layer may be a liquid crystal compound that is homogeneously oriented. The liquid crystal compound that can be homogeneously oriented may be a material made of a liquid crystal polymer or a material made of a liquid crystal monomer. The homogeneous orientation means a state in which the molecular long axis of the liquid crystal compound is oriented in the horizontal direction. In addition, the positive A layer preferably exhibits a smectic phase. Here, the smectic phase means a state in which molecules aligned in one direction have a phase structure.

[0024] The liquid crystal compound of the positive A layer includes a discotic liquid crystal material and a rod-shaped liquid crystal material, and is preferably a rod-shaped liquid crystal material that is easy to exhibit reverse dispersion. Examples of the polymerizable liquid crystal compound that exhibits reverse dispersion include those represented by the general formula (1) in JP 2019-73712 A and those represented by the general formula (II) in International Publication No. WO2017 / 043438.

[0025] The liquid crystal compound of the positive A layer can be a general-purpose material, for example, the compound represented by the general formula (I) described in JP-A-2008-297210, the compound represented by the general formula (1) described in JP-A-2010-84032, the liquid crystal compound A0 described in JP-A-2016-53709, etc. The liquid crystal compound of the positive A layer can also be the compounds shown in the following formulas (1) to (19).

[0026] [ka]

[0027] [ka]

[0028] [ka]

[0029] In the positive A layer, Re(450), Re(550) and Re(650) preferably satisfy the relationship of the following formula (A). That is, the positive A layer preferably has reverse dispersion. By using a positive A layer having reverse dispersion that satisfies the relationship of the following formula (A), it is possible to easily improve optical characteristics (e.g., visibility and antireflection properties) in the wavelength range outside 550 nm. Re(450) <Re(550)<Re(650) (A) The Re(450), Re(550) and Re(650) of the positive A layer are not particularly limited, but when the positive A layer is a λ / 4 retardation layer, it is preferable that they are in the following ranges. The positive A layer is preferably a λ / 4 retardation layer. The lower limit of the in-plane retardation of the λ / 4 retardation layer is preferably 100 nm or more, more preferably 110 nm or more, and even more preferably 135 nm or more. The upper limit of the in-plane retardation of the λ / 4 retardation layer is preferably 180 nm or less, more preferably 160 nm or less, and even more preferably 150 nm or less. By setting the in-plane retardation of the λ / 4 retardation layer within the above range, when the λ / 4 retardation layer is combined with a polarizer, the circular polarizing plate can easily exhibit an antireflection function.

[0030] The thickness of the positive A layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.5 μm or more, and the upper limit of the thickness of the positive A layer is preferably 5.0 μm or less, more preferably 4.0 μm or less, and even more preferably 3.0 μm or less. By setting the thickness of the positive A layer within the above range, the optical laminate can be made thinner, and the in-plane retardation of the λ / 4 retardation layer serving as the positive A layer can be easily set within the above range. The thickness of each layer such as the positive A layer, the positive C layer and the substrate can be calculated, for example, as the average value of 20 points by observing a cross-sectional image of the optical laminate with a scanning transmission electron microscope (STEM) or the like.

[0031] In this specification, the in-plane retardation, thickness retardation, haze, and total light transmittance refer to the average value of the measured values ​​at 16 points. The 16 measurement points are preferably centered on 16 intersections of lines drawn on the inner area of ​​the measurement sample, with a margin of 1 cm from the outer edge of the measurement sample, dividing the area inside the margin into 5 equal parts in the vertical and horizontal directions. When the measurement sample is a rectangle, it is preferable to measure the 16 intersections of lines drawn on the inner area of ​​the measurement sample, with a margin of 1 cm from the outer edge of the rectangle, dividing the area inside the margin into 5 equal parts in the vertical and horizontal directions, and calculate the average value. When the measurement sample is a shape other than a rectangle, such as a circle, ellipse, triangle, or pentagon, it is preferable to draw a rectangle with the maximum area inscribed in these shapes, and measure 16 points on the rectangle using the above method. The in-plane retardation and the retardation in the thickness direction can be measured, for example, by using a product called "RETS-100" manufactured by Otsuka Electronics Co., Ltd.

[0032] When measuring the in-plane retardation (Re) etc. using the RETS-100, it is preferable to prepare for the measurement in accordance with the following procedures (A1) to (A4). (A1) First, turn on the RETS-100 light source and leave it for 60 minutes or more to stabilize it. After that, select the rotating analyzer method and select θ mode (angle direction phase difference measurement and Rth calculation mode). By selecting this θ mode, the stage becomes a tilt rotation stage. (A2) Next, enter the following measurement conditions into the RETS-100. (Measurement conditions) Retardation measurement range: Rotating analyzer method Measurement spot diameter: φ5mm Tilt angle range: 0° Measurement wavelength range: 400nm~800nm -Average refractive index of the layer to be measured (for example, N=1.617 for PET film) Thickness: Thickness measured separately using SEM or optical microscope (A3) Next, background data is obtained without placing a sample in the instrument, in a closed system, and every time the light source is turned on. (A4) After that, the sample is placed on the stage inside the device and measured.

[0033] 《Formation method》 The retardation layers such as the positive A layer and the positive C layer described later can be formed by applying, drying, curing, and the like a retardation layer-forming coating liquid containing components constituting the retardation layer and a solvent. The content of the liquid crystal compound in the coating solution for forming the retardation layer is not particularly limited, but is preferably 5% by mass or more and 30% by mass or less in the coating solution. If the amount of the liquid crystal compound is less than 5% by mass, a large amount needs to be added during production, making production difficult, and a large amount of solvent needs to be removed, which tends to cause deterioration in reliability due to residual solvent. On the other hand, if the amount exceeds 30% by mass, the viscosity of the polymerizable liquid crystal composition becomes too high, making the workability of layer production poor. In addition, when the content of the liquid crystal compound relative to the solid content of the retardation layer is low, the alignment of the liquid crystal compound tends to decrease. Therefore, the content of the liquid crystal compound relative to the solid content mass (mass excluding the solvent) of the retardation layer forming coating solution is preferably 60% by mass or more, more preferably 80% by mass or more, and is preferably 95% by mass or less.

[0034] Other Ingredients The coating liquid for forming the retardation layer such as the positive A layer and the positive C layer described later may contain a polymerization initiator, a leveling agent, an alignment promoter, and the like.

[0035] -Polymerization initiator- The aligned liquid crystal compound is preferably fixed while maintaining the aligned state by a polymerization reaction. The polymerization reaction includes a thermal polymerization reaction using a thermal polymerization initiator and a photopolymerization reaction using a photopolymerization initiator. Among these, a photopolymerization reaction is preferred. Examples of the photopolymerization initiator include α-carbonyl compounds (see U.S. Pat. Nos. 2,367,661 and 2,367,670), acyloin ethers (see U.S. Pat. No. 2,448,828), α-hydrocarbon substituted aromatic acyloin compounds (see U.S. Pat. No. 2,722,512), polynuclear quinone compounds (see U.S. Pat. Nos. 3,046,127 and 2,951,758), combinations of triaryl imidazole dimers and p-aminophenyl ketones (see U.S. Pat. No. 3,549,367), acridine and phenazine compounds (see JP-A-60-105,667 and U.S. Pat. No. 4,239,850), and oxadiazole compounds (see U.S. Pat. No. 4,212,970).

[0036] When the content of the polymerization initiator is small, the curing tends to be insufficient, and when the content of the polymerization initiator is large, the alignment of the liquid crystal compound tends to be reduced. Therefore, the amount of the polymerization initiator used is preferably 0.01% by mass or more, more preferably 0.5% by mass or more, and the upper limit is preferably 20% by mass or less, more preferably 10% by mass or less, based on the total solid content of the retardation layer.

[0037] -Leveling agent- The leveling agent includes a fluorine-based leveling agent and a silicon-based leveling agent. When the content of the leveling agent is low, sufficient leveling properties tend not to be obtained, and when the content of the leveling agent is high, problems such as reduced defoaming properties tend to occur. Therefore, the content of the leveling agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, based on the total solid content of the retardation layer.

[0038] <Ultraviolet absorbing layer> In the optical laminate of the present invention, the ultraviolet absorbing layer is disposed at a position in contact with the positive A layer. By disposing the ultraviolet absorbing layer at a position in contact with the positive A layer, it is possible to suppress the retardation of the positive A layer from changing over time. The reason why this effect occurs will be explained below.

[0039] First, the reason why the retardation of the positive A layer changes over time is thought to be that when forming the positive A layer, it is difficult to completely complete the reaction of the polymerizable liquid crystal compound in the positive A layer, and the remaining unreacted material gradually reacts due to ultraviolet rays contained in external light, etc. For this reason, the retardation of a normal positive A layer changes over time, and the anti-reflection performance of a circular polarizing plate formed by combining the positive A layer and a polarizer cannot be maintained over time. On the other hand, by disposing the ultraviolet absorbing layer at a position in contact with the positive A layer, the above-mentioned problems can be suppressed. The reason for this is considered to be as follows. First, the ultraviolet absorber in the ultraviolet absorbing layer generates heat when it absorbs ultraviolet light. If the ultraviolet absorbing layer is disposed in contact with the positive A layer, the heat can promote the reaction of the polymerizable liquid crystal compound in the positive A layer. That is, by disposing the ultraviolet absorbing layer in contact with the positive A layer, the reaction of the unreacted polymerizable liquid crystal compound in the positive A layer can be promoted at the stage of forming the optical laminate, and the decrease in the retardation of the positive A layer after forming the optical laminate can be suppressed. In order to facilitate the above-mentioned effect, it is preferable, for example, to "set the transmittance of the optical laminate at a wavelength of 405 nm in the range described below," "set the absorbance of the ultraviolet absorbing layer at a wavelength of 405 nm in a predetermined range," and "provide a predetermined difference between the maximum absorption wavelength of the ultraviolet absorber and the absorption wavelength of the initiator of the polymerizable liquid crystal compound in the positive A layer." Another reason why it is preferable to dispose the ultraviolet absorbing layer at a position in contact with the positive A layer is that a part of the ultraviolet absorber penetrates into the positive A layer. That is, it is considered that the light resistance of the polymerizable liquid crystal compound in the positive A layer is improved by the penetration of a part of the ultraviolet absorber into the positive A layer, and the heat generated when the ultraviolet absorber absorbs ultraviolet light is easily transmitted to the polymerizable liquid crystal compound in the positive A layer.

[0040] In order to easily achieve the above-mentioned effects, the optical laminate is preferably manufactured by a process including the following (1) or (2). By manufacturing the optical laminate by a process including the following (1) or (2), ultraviolet light and heat act simultaneously on the unreacted polymerizable liquid crystal compound contained in the positive A layer, making it easier to promote the reaction of the compound. From the viewpoint of easily achieving the above-mentioned effects, it is more preferable to manufacture the optical laminate by a process including the following (2). (1) A coating solution for forming a positive A layer is directly applied onto an ultraviolet absorbing layer, dried, and then irradiated with ultraviolet light to form a positive A layer. (2) A coating solution for forming an ultraviolet absorbing layer is directly applied onto the positive A layer, dried, and then irradiated with ultraviolet light to form an ultraviolet absorbing layer. In either process, the important point for suppressing the change in retardation of the positive A layer over time is to form a laminate having a configuration in which the ultraviolet absorbing layer and the positive A layer are in direct contact with each other.

[0041] When the optical laminate produced by the process including the above (1) or (2) has a positive C layer, the order of forming the positive C layer is not particularly limited. The optical laminate including the positive C layer can be produced, for example, by the following methods (Z1) and (Z2). (Z1) A method in which a laminate Y is prepared by forming a positive C layer on a separately prepared substrate, and the laminate Y is then bonded to the positive A layer (1) or the ultraviolet absorbing layer (2). (Z2) A method in which a coating liquid for forming a positive C layer is applied onto the ultraviolet absorbing layer of (2), dried, and then irradiated with ultraviolet light to form a positive C layer.

[0042] The ultraviolet absorbing layer may be an alignment layer for the positive A layer. By adopting this configuration, the ultraviolet absorbing layer and the alignment layer for the positive A layer are used together, and the optical laminate can be made thinner. In addition, when having this configuration, it is preferable to arrange the positive C layer on the opposite side of the ultraviolet absorbing layer with respect to the positive A layer.

[0043] When the optical laminate has a positive C layer, the ultraviolet absorbing layer may be an alignment layer for the positive C layer. By adopting this configuration, the ultraviolet absorbing layer and the alignment layer for the positive C layer are used together, and the optical laminate can be made thinner. In addition, when having this configuration, it is preferable to arrange the positive C layer on the opposite side of the positive A layer with respect to the ultraviolet absorbing layer.

[0044] The ultraviolet absorbing layer preferably contains an ultraviolet absorbing agent and a binder component.

[0045] <Ultraviolet absorbing agent> The ultraviolet absorbent preferably has a lower limit of the maximum absorption wavelength of 350 nm or more, more preferably 365 nm or more, and preferably has an upper limit of the maximum absorption wavelength of 405 nm or less, more preferably 403 nm or less. That is, in this specification, the ultraviolet absorbent includes those having a maximum absorption wavelength in the short wavelength region of visible light.

[0046] The ultraviolet absorbent preferably has a narrow absorption wavelength range. Specifically, when the absorbance at the maximum absorption wavelength is defined as X, the wavelength range where the absorbance shows X / 2 (so-called full width at half maximum) is preferably 70 nm or less, more preferably 65 nm or less. The lower limit of the wavelength range in which the absorbance shows X / 2 is not particularly limited, but is usually about 20 nm, and preferably 30 nm or more. The absorbance can be measured, for example, using a solution prepared by dissolving 10 mg of an ultraviolet absorber in 1000 ml of a solvent such as chloroform.

[0047] Examples of the ultraviolet absorbent include benzophenone compounds, benzoxazinone compounds, benzophenone compounds, anthracene compounds, benzotriazole compounds, indole compounds, and methine compounds. Among these, benzotriazole compounds, indole compounds, and methine compounds are preferred. As the benzotriazole compounds, sesamol-type benzotriazole compounds and resorcinol-type benzotriazoles are preferred, and sesamol-type benzotriazole compounds are more preferred. As the ultraviolet absorbent, those having a polymerizable functional group that can react with the binder component are also preferred.

[0048] The sesamol-type benzotriazole compound includes a compound in which sesamol is bonded to the nitrogen atom at the 2-position of the benzotriazole ring (sesamol-type benzotriazole monomer), and a polymer of a composition containing the compound. The sesamol-type benzotriazole monomer includes a compound represented by the following general formula (I).

[0049] [ka]

[0050] [In formula (I), R 1 R represents a hydrogen atom or a methyl group. 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms or a linear or branched oxyalkylene group having 1 to 6 carbon atoms.)]

[0051] Examples of the resorcinol-type benzotriazole compound include a compound in which resorcinol is bonded to the nitrogen atom at the 2-position of the benzotriazole ring (resorcinol-type benzotriazole monomer), and a polymer composition containing the compound. Examples of the resorcinol-type benzotriazole monomer include the compound represented by the following general formula (II).

[0052] [ka]

[0053] [In formula (II), R 3 R represents a hydrogen atom or a methyl group. 4 R represents a linear or branched alkylene group having 1 to 6 carbon atoms. 5 represents a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms.)]

[0054] The composition containing the sesamol-type benzotriazole monomer and the composition containing the resorcinol-type benzotriazole monomer may contain other monomers. Examples of other monomers include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; and hydroxyl group-containing unsaturated monomers such as hydroxyethyl (meth)acrylate, hydroxypropylethyl (meth)acrylate, hydroxybutyl (meth)acrylate, and caprolactone-modified hydroxy(meth)acrylate.

[0055] The polymerization method for copolymerizing the composition containing a sesamol-type benzotriazole monomer or the composition containing a resorcinol-type benzotriazole monomer can be a conventionally known solution polymerization method, emulsion polymerization method, suspension polymerization method, bulk polymerization method, etc., and is not particularly limited.

[0056] Examples of the benzotriazole-based compounds, indole-based compounds and methine-based compounds include "BONASORB UA3912" (trade name) manufactured by Orient Chemical Industries Co., Ltd. and "FDB009" (trade name) manufactured by Yamada Chemical Industries Co., Ltd.

[0057] The content of the ultraviolet absorber is preferably 2 to 25 parts by mass, more preferably 3 to 20 parts by mass, and further preferably 5 to 15 parts by mass, relative to 100 parts by mass of the binder component. By making the content of the ultraviolet absorber 2 parts by mass or more, the heat generating action of the ultraviolet absorber described above is enhanced, and the effect of the present invention can be easily exhibited. Also, by making the content of the ultraviolet absorber 25 parts by mass or less, when the ultraviolet absorbing layer is used as an alignment layer, it is possible to easily suppress the deterioration of the alignment function.

[0058] <Binder components> The binder component is not particularly limited, and resins, liquid crystal compounds, and the like can be used. When the ultraviolet absorbing layer is made to function as an alignment layer for a positive A layer or an alignment layer for a positive C layer, the binder component preferably contains a component that functions as an alignment agent.

[0059] Binder components capable of functioning as an alignment agent for the positive A layer include photodimerization-type materials such as polycinnamate compounds. Examples of the binder component that can function as an alignment agent for the positive C layer include materials that form an LB film (Langmuir-Blodgett film), polyimide, and the like.

[0060] In addition, a cured product of a curable resin composition can be used as a binder component that can function in common as an alignment agent for the positive A layer and the positive C layer. Examples of the curable resin composition include a heat-curable resin composition and an ionizing radiation-curable resin composition, and the ionizing radiation-curable resin composition is preferred from the viewpoint of scratch resistance.

[0061] The thermosetting resin composition is a composition that contains at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to the curable resin as required.

[0062] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). Examples of the ionizing radiation curable functional group include ethylenically unsaturated bond groups such as (meth)acryloyl groups, vinyl groups, and allyl groups, as well as epoxy groups and oxetanyl groups. The ionizing radiation curable compound is preferably a compound having an ethylenically unsaturated bond group, more preferably a compound having two or more ethylenically unsaturated bond groups, and even more preferably a polyfunctional (meth)acrylate compound having two or more ethylenically unsaturated bond groups. That is, the ultraviolet absorbing layer preferably contains a cured product of a polyfunctional (meth)acrylate compound as a binder component. As the polyfunctional (meth)acrylate compound, either a monomer or an oligomer can be used. The ionizing radiation means electromagnetic waves or charged particle beams having an energy quantum capable of polymerizing or crosslinking molecules, and usually ultraviolet rays (UV) or electron beams (EB) are used, but other types of radiation such as electromagnetic waves, such as X-rays and γ-rays, and charged particle beams, such as α-rays and ion beams, can also be used. In this embodiment, it is preferable to use ultraviolet rays (UV).

[0063] Among the polyfunctional (meth)acrylate compounds, examples of bifunctional (meth)acrylate monomers include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxydiacrylate, bisphenol A tetrapropoxydiacrylate, and 1,6-hexanediol diacrylate. Examples of trifunctional or higher (meth)acrylate monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate. The (meth)acrylate monomer may have a part of its molecular skeleton modified, and may be modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, or the like.

[0064] Examples of the polyfunctional (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. The urethane (meth)acrylate can be obtained, for example, by reacting a polyhydric alcohol and an organic diisocyanate with a hydroxy (meth)acrylate. In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting a tri- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with (meth)acrylic acid, (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a polybasic acid and (meth)acrylic acid, and (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a phenol and (meth)acrylic acid.

[0065] The thickness of the ultraviolet absorbing layer is preferably about 0.2 μm or more and 5.0 μm or less. When the ultraviolet absorbing layer is used as an alignment layer, the thickness is preferably as follows. First, when the ultraviolet absorption layer is used as the alignment layer of the positive A layer, the thickness of the ultraviolet absorption layer preferably has a lower limit of 0.2 μm or more, more preferably 0.25 μm or more, still more preferably 0.3 μm or more, and an upper limit of preferably 2.0 μm or less, more preferably 1.0 μm or less. When the thickness is less than 0.2 μm, the positive A layer tends to have poor alignment. On the other hand, when the thickness exceeds 2.0 μm, it tends to be difficult to coat uniformly.

[0066] Also, when the ultraviolet absorption layer is used as the alignment layer of the positive C layer, the thickness of the ultraviolet absorption layer preferably has a lower limit of 2.0 μm or more, more preferably 2.2 μm or more, still more preferably 2.5 μm or more, and an upper limit of preferably 5.0 μm or less, more preferably 4.5 μm or less, still more preferably 4.0 μm or less. When the thickness is less than 2.0 μm, the positive C layer tends to have poor alignment. On the other hand, when the thickness exceeds 5.0 μm, it tends to be difficult to coat uniformly.

[0067] When the ultraviolet absorption layer acts as an alignment layer, it is preferable to impart an alignment control force as necessary. The means for imparting the alignment control force can be those conventionally known, and examples include the rubbing method, the photo-alignment method, the shaping method, and the like.

[0068] <Positive C layer> From the viewpoint of improving the visibility in the oblique direction, the optical laminate may have a positive C layer. The positive C layer is a layer that satisfies the relationship of Nx ≒ Ny < Nz.

[0069] The location of the positive C layer in the optical laminate is not particularly limited. For example, there are embodiments where it is disposed on the side opposite to the ultraviolet absorption layer with respect to the positive A layer (Figure 1), embodiments where it is disposed on the side opposite to the ultraviolet absorption layer with respect to the positive A layer (Figure 2).

[0070] As shown in Fig. 1, when the positive C layer is disposed on the opposite side of the ultraviolet absorbing layer with respect to the positive A layer, the optical laminate preferably has a configuration in which the positive A layer, the ultraviolet absorbing layer, the adhesive layer, and the positive C layer are laminated in this order. In this case, it is preferable that the ultraviolet absorbing layer acts as an alignment layer for the positive A layer.

[0071] As shown in Fig. 2, when the positive C layer is disposed on the opposite side of the positive A layer with respect to the ultraviolet absorbing layer, it is preferable that the positive C layer is in contact with the ultraviolet absorbing layer. In this case, it is preferable that the ultraviolet absorbing layer acts as an alignment layer for the positive C layer. In this case, it is preferable that the optical laminate has a configuration in which the positive C layer, the ultraviolet absorbing layer, and the positive A layer are laminated in this order.

[0072] In order to prevent the alignment from being deteriorated, the positive C layer preferably contains a constitutional unit derived from a liquid crystal compound as a main component. The main component means that the main component is 50% by mass or more of the total solid content of the positive C layer, preferably 65% ​​by mass or more, and more preferably 80% by mass or more.

[0073] As described above, the liquid crystal compound forming the positive C layer preferably contains a polymerizable liquid crystal compound having a polymerizable functional group in the molecule, and more preferably contains a polymerizable liquid crystal compound having two or more polymerizable functional groups in the molecule. As described above, it is particularly preferable that the liquid crystal compound forming the positive C layer has a polymerizable functional group at the end. As described above, the liquid crystal compound forming the positive C layer may be used alone or in combination of two or more.

[0074] The liquid crystal compound of the positive C layer may be a liquid crystal compound that is vertically aligned (homeotropic alignment). The liquid crystal compound preferably exhibits a smectic phase or a nematic phase, and more preferably exhibits a smectic phase. The smectic phase provides a highly ordered layer structure in which the centers of gravity of the liquid crystal molecules are aligned, which makes it easier for the positive C layer to assume a homeotropic alignment. The liquid crystal compound in the positive C layer is preferably a rod-shaped liquid crystal compound.

[0075] Preferred examples of rod-shaped liquid crystal compounds include azomethines, azoxys, cyanobiphenyls, cyanophenyl esters, benzoates, cyclohexane carboxylic acid phenyl esters, cyanophenylcyclohexanes, cyano-substituted phenylpyrimidines, alkoxy-substituted phenylpyrimidines, phenyldioxanes, tolanes, and alkenylcyclohexylbenzonitriles. Not only the above-mentioned low molecular weight liquid crystal compounds, but also polymeric liquid crystal compounds can be used. It is more preferable to fix the orientation of the rod-shaped liquid crystal compound by polymerization. It is preferable that the liquid crystal compound has a partial structure that can undergo polymerization or crosslinking reaction by actinic rays, electron beams, heat, etc., and more preferably has a polymerizable group. The number of the partial structures is preferably 1 to 6, and more preferably 1 to 3. As the polymerizable rod-like liquid crystal compound, compounds described in Makromol.Chem., Vol. 190, p. 2255 (1989), Advanced Materials, Vol. 5, p. 107 (1993), U.S. Pat. Nos. 4,683,327, 5,622,648, and 5,770,107, International Publication WO 95 / 22586, 95 / 24455, 97 / 00600, 98 / 23580, and 98 / 52905, JP-A Nos. 1-272551, 6-16616, 7-110469, 11-80081, and 2001-328973 can be used. Specific examples of the rod-shaped liquid crystal compound include the compounds represented by the above formulas (1) to (19).

[0076] The positive C layer preferably contains a vertical alignment promoter to facilitate uniform vertical alignment of the molecules of the liquid crystal compound. Examples of the vertical alignment promoter include a boronic acid compound and / or an onium salt. The vertical alignment agent is preferably present in an amount of 0.1% by mass to 25% by mass, more preferably 0.5% by mass to 20% by mass, based on the total solid content of the positive C layer.

[0077] The lower limit of Rth(550) of the positive C layer is preferably −100 nm or more, more preferably −90 nm or more, and the upper limit is preferably −50 nm or less, more preferably −60 nm or less. By setting Rth(550) of the positive C layer in this range, visibility in oblique directions can be easily improved.

[0078] In order not to affect the in-plane retardation of the positive A layer, it is preferable that the positive C layer has a small Re(550), and the Re(550) is preferably 20 nm or less, more preferably 10 nm or less, even more preferably 5 nm or less, and still more preferably 2 nm or less.

[0079] The thickness of the positive C layer is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.10 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. By setting the thickness of the positive C layer within the above range, the optical laminate can be made thinner and the Rth(550) of the positive C layer can be easily set within the above range.

[0080] <Base material> The optical laminate may have a substrate. The substrate is preferably a plastic film. Examples of polymers that make up plastic films include cellulose acylate, polycarbonate-based polymers, polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate, acrylic-based polymers such as polymethyl methacrylate, styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymer (AS resin), polyolefin-based polymers such as polyethylene, polypropylene and ethylene-propylene copolymer, vinyl chloride-based polymers, amide-based polymers such as nylon and aromatic polyamide, imide-based polymers, sulfone-based polymers, polyethersulfone-based polymers, polyetheretherketone-based polymers, polyphenylene sulfide-based polymers, vinylidene chloride-based polymers, vinyl alcohol-based polymers, vinyl butyral-based polymers, arylate-based polymers, polyoxymethylene-based polymers, and epoxy-based polymers.

[0081] The substrate, for example, serves as a support for the positive A layer, the ultraviolet absorbing layer, etc. However, in consideration of the thinning of the image display device, the substrate is preferably peelable. In other words, the substrate is preferably peelable so that it does not remain in the image display device. For example, if the positive A layer, the ultraviolet absorbing layer, etc. are bonded to another member (e.g., a polarizer) of the image display device, and then the peelable substrate is peeled off, this can contribute to the thinning of the image display device. The peelable substrate may be, for example, the above-mentioned plastic film itself, or the above-mentioned plastic film whose surface has been subjected to a release treatment with a general-purpose release agent or the like.

[0082] From the viewpoint of handleability, the lower limit of the thickness of the substrate is preferably 15 μm or more, more preferably 25 μm or more, even more preferably 30 μm or more, and even more preferably 40 μm or more, and from the viewpoint of lengthening during the production of the optical laminate, the upper limit is preferably 150 μm or less, more preferably 125 μm or less, and even more preferably 100 μm or less. In the case where the substrate is not to remain inside the image display device, the thickness of the substrate is preferably 15 μm or more and 100 μm or less. In addition, when the substrate is to remain in the image display device, the thickness of the substrate is preferably 15 μm or more and 60 μm or less. In particular, when the optical laminate is applied to a foldable type image display device, a rollable type image display device, or the like, the thickness of the substrate is preferably within the above range (15 μm or more and 60 μm or less) in consideration of the balance between flexibility and strength.

[0083] <Other layers> The optical laminate may have other layers, such as a gas barrier layer, an adhesive layer, a surface protective layer, an alignment layer, etc., as long as the effects of the present invention are not impaired.

[0084] <Physical properties of optical laminate> The optical laminate preferably has a lower limit of transmittance at a wavelength of 405 nm of 2.0% or more, more preferably 5.0% or more, and preferably has an upper limit of transmittance at a wavelength of 405 nm of 85.0% or less, more preferably 80.0% or less.

[0085] If the transmittance at a wavelength of 405 nm is too low, the amount of ultraviolet absorber added in the ultraviolet absorbing layer becomes excessive, and there is a concern that the function of the ultraviolet absorbing layer as an alignment layer will be reduced. Also, if the transmittance at a wavelength of 405 nm is too low, there is a concern that the thickness of the ultraviolet absorbing layer will be too thick, which will hinder the thinning of the image display device. From these viewpoints, the transmittance at a wavelength of 405 nm is preferably 2.0% or more. On the other hand, if the transmittance at a wavelength of 405 nm is too high, the heat generation effect caused by the ultraviolet absorber in the ultraviolet absorbing layer absorbing ultraviolet light may be insufficient, and it may be difficult to suppress the fluctuation of retardation over time. From this viewpoint, the transmittance at a wavelength of 405 nm is preferably 85.0% or less.

[0086] The optical layered body preferably has a haze according to JIS K7136:2000 of 1.0% or less, more preferably 0.9% or less, and even more preferably 0.8% or less. Furthermore, the optical laminate preferably has a total light transmittance according to JIS K7361-1:1997 of 80% or more, more preferably 85% or more, and even more preferably 90% or more. By setting the haze or total light transmittance of the optical laminate within the above range, visibility of the image display device can be ensured.

[0087] The difference between the Re(550) of the optical laminate before and after the heat resistance reliability test of the examples is preferably 2.0 nm or less, more preferably 1.5 nm or less, and even more preferably 1.0 nm or less. In the optical laminate, the difference between the Re(550) before the light resistance reliability test of the examples and the Re(550) after the test is preferably 2.0 nm or less, more preferably 1.5 nm or less, and even more preferably 1.0 nm or less. By setting the difference in Re(550) before and after the heat reliability test and the difference in Re(550) before and after the light reliability test within the above ranges, the retardation of the optical laminate is prevented from changing over time, and the anti-reflection performance of the circular polarizing plate formed by combining the optical laminate and a polarizer can be easily prevented from decreasing. In other words, by setting the difference in Re(550) before and after the heat reliability test and the difference in Re(550) before and after the light reliability test within the above ranges, the visibility of the image display device can be easily maintained in a good state.

[0088] For the optical laminate, the difference between Re(450) / Re(550) before the heat resistance reliability test of the examples and Re(450) / Re(550) after the test is preferably 0.050 or less, more preferably 0.035 or less, and even more preferably 0.010 or less. For the optical laminate, the difference between Re(450) / Re(550) before the light resistance reliability test of the examples and Re(450) / Re(550) after the test is preferably 0.050 or less, more preferably 0.035 or less, and even more preferably 0.010 or less. Re(450) / Re(550) contributes to the color of the image display panel. Therefore, by setting the difference between Re(450) / Re(550) before and after the heat resistance reliability test and the difference between Re(450) / Re(550) before and after the light resistance reliability test within the above range, it is possible to easily suppress the color of the image display panel from changing over time. When Re(450) and Re(550) change due to the above test, usually, both Re(450) and Re(550) increase or decrease, and there are few cases where only one of them increases or decreases. Therefore, when both Re(450) and Re(550) change due to the above test, as a result, Re(450) / Re(550) may not change. In other words, a small difference between Re(450) / Re(550) before and after the above test does not necessarily indicate that the phase difference does not change due to the above test. On the other hand, the difference in Re(550) before and after the test indicates that the phase difference is not changed by the test. Therefore, in the present invention, it is more important that the difference in Re(550) before and after the test is small.

[0089] <Size, shape, etc.> The optical laminate may be in the form of a sheet or a roll. The size of the sheets is not particularly limited, but generally, the size is about 2 to 500 inches diagonally. The width and length of the roll are not particularly limited, but generally, the width is about 500 to 3000 mm, and the length is about 500 to 5000 m. The shape of the sheets is also not particularly limited, and may be, for example, polygonal (triangle, square, pentagon, etc.) or circular, or may be a random, indeterminate shape.

[0090] [Polarizing plate] The polarizing plate of the present invention has a polarizer, a transparent protective plate A arranged on one side of the polarizer, and a transparent protective plate B arranged on the other side of the polarizer, and either the transparent protective plate A or the transparent protective plate B is the optical laminate of the present invention described above.

[0091] FIG. 3 is a cross-sectional view showing an embodiment of the polarizing plate of the present invention. The polarizing plate 200 in Fig. 3 includes a polarizer 80, a transparent protective plate A (81) disposed on one side of the polarizer, and a transparent protective plate B (82) disposed on the other side of the polarizer. The transparent protective plate B (81) in Fig. 3 is an optical laminate 100.

[0092] <Polarizer> Examples of polarizers include sheet-type polarizers such as polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, and saponified ethylene-vinyl acetate copolymer films dyed with iodine or the like and stretched, wire-grid-type polarizers made of a large number of metal wires arranged in parallel, coating-type polarizers coated with lyotropic liquid crystal or a dichroic guest-host material, and multilayer thin-film-type polarizers. These polarizers may be reflective polarizers that have the function of reflecting polarized components that are not transmitted.

[0093] <Transparent protection plate> A transparent protective plate A is disposed on one side of the polarizer, and a transparent protective plate B is disposed on the other side of the polarizer. One of the transparent protective plate A and the transparent protective plate B is the above-mentioned optical laminate of the present invention.

[0094] Examples of the transparent protective plate A and the transparent protective plate B other than the optical laminate include plastic films and glass. Examples of the plastic film include polyester films, polycarbonate films, cycloolefin polymer films, and acrylic films, and from the viewpoint of mechanical strength, stretched films of these films are preferred. Examples of the glass include alkali glass, nitride glass, soda-lime glass, borosilicate glass, and lead glass. In addition, it is preferable that the glass as the transparent protective plate protecting the polarizer is also used as other members of the image display device (for example, the glass substrate of the liquid crystal display element, the front panel of the image display device). The polarizer and the transparent protective plate are preferably attached to each other via an adhesive, which may be a general-purpose adhesive, and is preferably a PVA-based adhesive.

[0095] When the positive A layer is a λ / 4 retardation layer, it is preferably arranged so that the absorption axis of the polarizer and the slow axis of the positive A layer are at 45 degrees ± 5 degrees, more preferably at 45 degrees ± 3 degrees, and even more preferably at 45 degrees ± 1 degree. By arranging them in the above-mentioned angle relationship, it can function as a circular polarizing plate.

[0096] The polarizing plate of the present invention is preferably used as a polarizing plate arranged on the light exit surface side of a display element. When used as described above, the transparent protective plate on the light incident surface side based on the polarizer is preferably the optical laminate of the present invention described above. In the polarizing plate, the optical laminate is preferably arranged so that the ultraviolet absorbing layer is closer to the light exit surface side than the positive A layer.

[0097] [Display Panel] The display panel of the present invention comprises the above-mentioned optical layered body of the present invention disposed on the light-emitting surface side of a display element. In the display panel, the optical laminate is preferably disposed so that the ultraviolet absorbing layer is closer to the light exit surface than the positive A layer.

[0098] 4 is a cross-sectional view showing an embodiment of a display panel 500 of the present invention. The display panel 500 in FIG. 4 has an optical laminate 100 laminated on the light emitting surface side of a display element 300.

[0099] When the display element of the display panel is a liquid crystal display element, a backlight (not shown) is required on the back of the liquid crystal display element. Either an edge-lit backlight or a direct-type backlight can be used as the backlight. Examples of the light source for the backlight include LED and CCFL, but a backlight using quantum dots as the light source is preferred because it is easy to improve color reproducibility.

[0100] The display panel preferably has a polarizer on the surface of the optical laminate opposite to the display element. By adopting such a configuration, it is possible to impart an external light anti-reflection function to the image display device and to suppress loss of color when viewed from an oblique angle.

[0101] <Display element> Examples of the display element include a liquid crystal display element, an organic EL display element, an inorganic EL display element, a plasma display element, an electronic paper display element, an LED display element (such as a micro LED), a display element using quantum dots, etc. These display elements may have a touch panel function inside the display element.

[0102] [Image display device] The image display device of the present invention is not particularly limited as long as it is equipped with the display panel of the present invention, but it preferably comprises the display panel of the present invention, a drive control unit electrically connected to the display panel, and a housing that accommodates these.

[0103] The image display device may be a foldable image display device or a rollable image display device. The image display device may also be an image display device with a touch panel. EXAMPLES

[0104] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples. In addition, "parts" and "%" are based on mass unless otherwise specified.

[0105] 1. Measurement and Evaluation The optical laminates obtained in the examples and comparative examples were subjected to the following measurements and evaluations. The results are shown in Table 1.

[0106] 1-1. Heat resistance reliability The Re(450), Re(550), and Re(650) of the optical laminates of the examples and comparative examples were measured using a product name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. Note that the in-plane retardation of the layers other than the positive A layer of the optical laminates of the examples and comparative examples is approximately 0. Therefore, the Re(450), Re(550), and Re(650) of the optical laminates can be regarded as the Re(450), Re(550), and Re(650) of the positive A layer. Next, a heat resistance test was performed on the optical laminates of the examples and comparative examples by heat treatment in an oven at 80°C for 500 hours, and the Re(450), Re(550), and Re(650) of the optical laminates after the heat resistance test were measured. The atmosphere during the measurement of the in-plane retardation after the heat resistance test was a temperature of 23°C±5°C and a humidity of 50%±10%. Furthermore, the samples were allowed to acclimate to the atmosphere for 30 minutes or more before measuring the in-plane retardation. The difference between the initial Re(550) and the Re(550) after the heat resistance test is shown as ΔRe(550) in Table 1. Also, the difference between the initial Re(450) / Re(550) and the Re(450) / Re(550) after the heat resistance test is shown as ΔRe(450) / Re(550) in Table 1.

[0107] 1-2. Light resistance reliability First, in the same manner as in 1-1, the Re(450), Re(550), and Re(650) of the optical laminates of the examples and comparative examples were measured. Next, the optical laminates of the examples and comparative examples were subjected to a 78-hour light resistance test (relative humidity: 50% RH, black panel temperature: 63°C, glass filter A described in JIS B7753 was used, irradiance: 255 W / m) using a Sunshine Weather Meter (manufactured by Suga Test Instruments Co., Ltd., device name: S80). 2 (Adjusted to continuous irradiation at a wavelength of 300 nm to 400 nm) was performed, and the Re(450), Re(550), and Re(650) of the optical laminate after the light resistance test were measured. The atmosphere during the measurement of the in-plane retardation after the light resistance test was set to a temperature of 23°C ± 5°C and a humidity of 50% ± 10%. Furthermore, the sample was allowed to acclimate to the atmosphere for 30 minutes or more before the measurement of the in-plane retardation. The difference between the initial Re(550) and the Re(550) after the light fastness test is shown as ΔRe(550) in Table 1. Also, the difference between the initial Re(450) / Re(550) and the Re(450) / Re(550) after the light fastness test is shown as ΔRe(450) / Re(550) in Table 1.

[0108] 2. Compound synthesis 2-1. Synthesis of polymerizable liquid crystal compounds Based on the synthesis of compound 4 in Example 4 of Japanese Patent No. 5,962,760, the polymerizable liquid crystal compound (A) shown below was synthesized.

[0109] [ka]

[0110] 2-2. Synthesis of UV absorbers A 200mL four-neck flask was equipped with a ball condenser, a mercury thermometer, and a stirrer, and 4.0g (0.013 mol) of 6-[5-(2-hydroxyethyl)-2H-benzotriazol-2-yl]benzo[1,3]dioxol-5-ol, 40mL of toluene, 1.8g (0.021 mol) of methacrylic acid, and 0.4g (0.004 mol) of methanesulfonic acid were added and refluxed for 4 hours at 110°C to 115°C. Next, 30mL of water and 0.6g (0.006 mol) of sodium carbonate were added, and the mixture was left to stand, and the lower aqueous layer was separated and removed. 0.2g of activated carbon was added, and the mixture was refluxed and stirred to decolorize. After filtration, 40 mL of toluene was collected from the filtrate under reduced pressure, 100 mL of isopropyl alcohol was added, and the precipitated crystals were filtered and washed with 40 mL of isopropyl alcohol, then dried under reduced pressure at 40° C. to obtain 4.2 g of yellow crystals. The 4.2 g of yellow crystals were repulped and washed with isopropyl alcohol and dried under reduced pressure at 40° C. to obtain 3.4 g of 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl methacrylate (ultraviolet absorber (B-1), maximum absorption wavelength is 367.8 nm) as a sesamol-type benzotriazole monomer.

[0111] 3. Preparation of Optical Laminate [Example 1] A coating liquid 1 for forming an ultraviolet absorbing layer, which was prepared by adding an ultraviolet absorbing agent (B-1) to a composition containing a polycinnamate compound (solid content 4%, diluted with propylene glycol monomethyl ether) was applied onto a PET film having a thickness of 80 μm to form a coating film. The content of the ultraviolet absorbing agent (B-1) in the coating liquid 1 for forming an ultraviolet absorbing layer was 7.5 parts by mass relative to 100 parts by mass of the polycinnamate compound. The resulting coating film was then dried at 120°C for 1 minute and exposed to polarized light at 20 mJ / cm 2 (310 nm) to form an ultraviolet absorbing layer for alignment of the positive A layer with a film thickness of 300 nm. Next, the positive A layer coating solution 1 described below was applied onto the ultraviolet absorbing layer using a bar coater so that the film thickness after drying was 2.5 μm, and then dried (120° C., 60 seconds), and then irradiated with ultraviolet light (integrated light amount: 400 mJ / cm 2 ). 2 ), a positive A layer was formed, and a laminate 1 having a PET film, an ultraviolet absorbing layer, and a positive A layer in this order was obtained.

[0112] <Positive A layer coating solution 1> 100 parts by mass of the polymerizable liquid crystal compound (A) obtained in 2-1 above Photopolymerization initiator 5 parts by weight (IGM Resins BV, product name "Omnirad 369") Toluene 500 parts by weight N-Methylpyrrolidone 400 parts by weight

[0113] Next, a coating solution for forming a vertical alignment film, which is made by adding 5 parts by mass of a photopolymerization initiator (IGM Resins BV, product name "Omnirad 907") to 100 parts by mass of pentaerythritol triacrylate (product name: PET-30) manufactured by Nippon Kayaku Co., Ltd., was applied onto a PET film having a thickness of 38 μm to form a coating film. The formed coating film was irradiated with ultraviolet light (accumulated light amount: 150 mJ / cm 2 ) to form a vertical alignment film having a thickness of 2 μm. Next, the following positive C layer forming coating solution 1 was applied onto the vertical alignment film by gravure coating so that the film thickness after drying was 0.6 μm, dried (40° C., 2 minutes), and irradiated with ultraviolet light (integral light amount: 150 mJ / cm 2 ). 2 ), a positive C layer was formed, and a laminate 2 having a PET film, a vertical alignment film, and a positive C layer in this order was obtained.

[0114] <Positive C layer coating solution 1> ·Polymerizable liquid crystal compound 100 parts by mass (Merck, product name: RMM28B, contains photopolymerization initiator) Methyl ethyl ketone 500 parts by weight Cyclohexanone 400 parts by weight

[0115] Next, the surface of the positive A layer side of the laminate 1 and the surface of the positive C layer side of the laminate 2 were laminated via an optically isotropic acrylic adhesive layer (thickness 5 um), and the PET films on both sides were peeled off to obtain the optical laminate of Example 1, which had a vertical alignment film, a positive C layer, an adhesive layer, a positive A layer, and an ultraviolet absorbing layer in this order.

[0116] [Example 2] A coating solution for forming a horizontal alignment film, which was made of a composition containing a polycinnamate compound (solid content 4%, diluted with propylene glycol monomethyl ether), was applied onto a PET film having a thickness of 80 μm to form a coating film. The resulting coating film was then dried at 120°C for 1 minute and exposed to polarized light at 20 mJ / cm 2 (310 nm) was irradiated to form a horizontal alignment film having a thickness of 300 nm. Next, the above-mentioned positive A layer coating solution 1 was applied onto the horizontal alignment film using a bar coater so that the film thickness after drying was 2.5 μm, and the film was dried (120° C., 60 seconds), and irradiated with ultraviolet light (integrated light amount: 400 mJ / cm 2 ). 2 ), forming a positive A layer. Next, on the positive A layer, a coating solution 2 for forming an ultraviolet absorbing layer was applied, which was prepared by adding 5 parts by mass of a photopolymerization initiator (IGM Resins BV, product name "Omnirad 907") and 5 parts by mass of an ultraviolet absorber (B-1) to 100 parts by mass of pentaerythritol triacrylate (product name: PET-30) manufactured by Nippon Kayaku Co., Ltd., to form a coating film. The formed coating film was irradiated with ultraviolet light (accumulated light amount: 150 mJ / cm2). 2 ) to form an ultraviolet absorbing layer for alignment of the positive C layer having a thickness of 3 μm. Next, the above-mentioned positive C layer forming coating solution 1 was applied onto the ultraviolet absorbing layer by gravure coating so that the film thickness after drying was 0.6 μm, dried (40° C., 2 minutes), and irradiated with ultraviolet light (integral light amount: 150 mJ / cm 2 ). 2 ), a positive C layer was formed, and a laminate 3 having a PET film, a horizontal alignment film, a positive A layer, an ultraviolet absorbing layer, and a positive C layer in this order was obtained. Next, the PET film of the laminate 3 was peeled off to obtain an optical laminate of Example 2 having a horizontal alignment film, a positive A layer, an ultraviolet absorbing layer, and a positive C layer in this order.

[0117] [Example 3] In Example 1, the ultraviolet absorber was changed from "ultraviolet absorber (B-1)" to "BONASORB UA3912, product name, indole-based compound, maximum absorption wavelength: 391 nm, manufactured by Orient Chemical Industries Co., Ltd.", and the content of the ultraviolet absorber was changed to 15 parts by mass per 100 parts by mass of the polycinnamate-based compound. The optical laminate of Example 3 was obtained in the same manner as in Example 1.

[0118] [Example 4] In Example 2, the ultraviolet absorber was changed from "ultraviolet absorber (B-1)" to "BONASORB UA3912, product name, indole-based compound, maximum absorption wavelength: 391 nm" manufactured by Orient Chemical Industries Co., Ltd., and the content of the ultraviolet absorber was changed to 15 parts by mass per 100 parts by mass of pentaerythritol triacrylate. The optical laminate of Example 4 was obtained in the same manner as in Example 2.

[0119] [Example 5] In Example 1, the ultraviolet absorber was changed from "ultraviolet absorber (B-1)" to "Yamada Chemical Co., Ltd.'s product name "FDB009", maximum absorption wavelength: 402 nm" and the content of the ultraviolet absorber was changed to 5 parts by mass per 100 parts by mass of the polycinnamate compound. The optical laminate of Example 5 was obtained in the same manner as in Example 1.

[0120] [Comparative Example 1] An optical laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that no ultraviolet absorber was added to the coating liquid forming the layer between the PET film and the positive A layer of the laminate 1. The optical laminate of Comparative Example 1 comprises a vertical alignment film, a positive C layer, a pressure sensitive adhesive layer, a positive A layer, and a horizontal alignment film in this order, and does not have an ultraviolet absorbing layer.

[0121] [Comparative Example 2] An optical laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that no ultraviolet absorber was added to the coating liquid forming the layer between the PET film and the positive A layer of the laminate 1 in Example 1, and an ultraviolet absorber (B-1) was added to the coating liquid for forming the vertical alignment film of the laminate 2. In Comparative Example 2, the content of the ultraviolet absorber (B-1) in the coating liquid for forming the vertical alignment film was 5 parts by mass relative to 100 parts by mass of pentaerythritol triacrylate. The optical laminate of Comparative Example 2 includes a vertical alignment film (ultraviolet absorbing layer), a positive C layer, a pressure-sensitive adhesive layer, a positive A layer, and a horizontal alignment film in this order. That is, the optical laminate of Comparative Example 2 has an ultraviolet absorbing layer, but the ultraviolet absorbing layer is not in contact with the positive A layer.

[0122] [Table 1]

[0123] From the results in Table 1, it can be confirmed that the optical laminates of the Examples can suppress the change in the retardation of the positive A layer over time when exposed to a high temperature environment and an environment where ultraviolet rays are received for a long period of time. In addition, among the Examples, it can be confirmed that Examples 2 and 4, which include a process of "directly applying a coating liquid for forming an ultraviolet absorbing layer onto the positive A layer, drying the coating liquid, and then irradiating the coating liquid with ultraviolet rays to form an ultraviolet absorbing layer", can further suppress the change in the retardation of the positive A layer over time. On the other hand, it can be confirmed that the optical laminate of Comparative Example 1 does not have an ultraviolet absorbing layer, and therefore cannot suppress the change over time in the retardation of the positive A layer. Also, the optical laminate of Comparative Example 2 has an ultraviolet absorbing layer, but the ultraviolet absorbing layer is not in contact with the positive A layer, and therefore it can be confirmed that the change over time in the retardation of the positive A layer due to heat cannot be suppressed. In addition, from Table 1, there is no significant difference in "ΔRe(450) / Re(550)" between the examples and the comparative examples. The reason for this is that, as described above, even if Re(450) and Re(550) fluctuate due to heat and light, both Re(450) and Re(550) increase or decrease, and as a result, the ratio "ΔRe(450) / Re(550)" is less likely to change. That is, in Table 1, it is important that the difference in "ΔRe(550)" is small in both the heat resistance reliability test and the light resistance reliability test. And, the optical laminate of the example is superior to the optical laminate of the comparative example in that the difference in "ΔRe(550)" is small in both the heat resistance reliability test and the light resistance reliability test. [Explanation of symbols]

[0124] 10: Positive A layer 20: UV absorbing layer 30: Positive C layer 40: Adhesive layer 80: Polarizer 81: Transparent protection plate A 82:Protective protection plate B 100: Optical laminate 200: Polarizing plate 300: Display element 500: Display panel

Claims

1. A positive A layer and an ultraviolet absorbing layer in contact with the positive A layer, The optical stack, wherein the UV absorbing layer is an alignment layer for the positive A layer.

2. The optical laminate according to claim 1 , wherein the ultraviolet absorbing layer has a thickness of 0.2 μm or more and 2.0 μm or less.

3. 3. The optical laminate according to claim 1, further comprising a positive C layer on the opposite side of the positive A layer from the ultraviolet absorbing layer.

4. An optical laminate described in any one of claims 1 to 3, wherein the ultraviolet absorbing layer contains an ultraviolet absorber and a binder component, and the binder component is a photodimerization type material.

5. An optical laminate described in any one of claims 1 to 3, wherein the ultraviolet absorbing layer contains an ultraviolet absorber and a binder component, and the binder component is a cured product of a curable resin composition.

6. 6. The optical laminate according to claim 1, wherein the transmittance at a wavelength of 405 nm is 2.0% or more and 80.0% or less.

7. 7. The optical laminate according to claim 1, wherein Re(550) is defined as the in-plane retardation of the positive A layer at a wavelength of 550 nm, and Re(550) is 135 nm or more and 150 nm or less.

8. The in-plane retardation of the positive A layer at a wavelength of 450 nm is defined as Re(450), the in-plane retardation of the positive A layer at a wavelength of 550 nm is defined as Re(550), and the in-plane retardation of the positive A layer at a wavelength of 650 nm is defined as Re(650). The optical laminate according to any one of claims 1 to 7, which satisfies the relationship of the following formula (A). Re(450)<Re(550)<Re(650) (A)

9. A polarizing plate having a polarizer, a transparent protective plate A arranged on one side of the polarizer, and a transparent protective plate B arranged on the other side of the polarizer, wherein either the transparent protective plate A or the transparent protective plate B is an optical laminate described in any one of claims 1 to 8.

10. A display panel comprising the optical laminate according to any one of claims 1 to 8 disposed on a light exit surface of a display element.

11. 11. The display panel according to claim 10, wherein the ultraviolet absorbing layer is disposed farther from the display element than the positive A layer.

12. An image display device comprising the display panel according to claim 10 or 11.

Citation Information

Patent Citations

  • Light emitting device and image forming apparatus using it

    JP2007080604A

  • Polychromatic organic light-emitting device

    JP2007294421A

  • Polarizing plate protective film, polarizing plate and liquid crystal display device

    JP2008134624A

  • Compound, optical film, and method for producing optical film

    JP2010031223A

  • Composition for alignment layer, method of manufacturing alignment layer, and optical anisotropic body

    JP2010096892A